ZACHARIAS’S PRAYER IN TWO NOVGORODIAN TRANSLATIONS (END OF THE 15TH – FIRST HALF OF THE 16TH CENTURY): SOME REFLECTIONS ON MULTIPLE TRANSLATIONS AND RE-TRANSLATIONS - Vittorio Springfield Tomelleri (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
The article examines the phenomenon of “multiple” translation using the example of two Church Slavic versions of Zacharias’s prayer, translated from Latin. The interlinear publication of both texts, carried out for the first time, is accompanied by a short philological and linguistic commentary providing a detailed analysis of the principal features of these two translations, which arose independently of each other in Novgorod, with a gap of some decades between them (end of the 15th – first half of the 16th century). When comparing the Novgorodian versions of the prayer, an interesting circumstance was revealed: if some discrepancies between the translations undoubtedly result from differences in the genre and function of the two translated works, certain lexical and grammatical deviations from the Latin model appear to be externally influenced by the existing Church Slavic text of the prayer, which was originally translated from Greek. For the correct understanding of these “new” versions, it is always necessary to constantly consider the possibility of strong interference from the “traditional text”, already existing in the written form as well as in the translators’ minds. Therefore, in this case we can only conditionally refer to translation in the literal sense of the word, designating a similar way of working as a peculiar case of “re-translation”.